2015
DOI: 10.1016/j.jmatprotec.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Laser microsculpting for the generation of robust diffractive security markings on the surface of metals

Abstract: a b s t r a c tWe report the development of a laser-based process for the direct writing ('microsculpting') of unique security markings (reflective phase holograms) on the surface of metals. In contrast to the common approaches used for unique marking of the metal products and components, e.g., polymer holographic stickers which are attached to metals as an adhesive tape, our process enables the generation of the security markings directly onto the metal surface and thus overcomes the problems with tampering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…In the present study, although there are similarities with the aforementioned studies [35,36] , the operation of the laser in a scanning instead of steady mode, the use of a different wavelength (1070 nm instead of 355 nm) and the use of different energy values (0.19-1 mJ on a beam diameter at focusing point of 80 μm, instead of 1-5 μJ on 11 μm) caused difference in the interaction mechanisms. More in detail, at high Le values (0.6 J/mm), the depth rapidly drops for increasing pulse energy after a Pe > 0.28 mJ (or equivalently a pulse power > 8 kW), in agreement to what observed by Wlodarczyk et al.…”
Section: Groove Profile Geometrysupporting
confidence: 54%
See 2 more Smart Citations
“…In the present study, although there are similarities with the aforementioned studies [35,36] , the operation of the laser in a scanning instead of steady mode, the use of a different wavelength (1070 nm instead of 355 nm) and the use of different energy values (0.19-1 mJ on a beam diameter at focusing point of 80 μm, instead of 1-5 μJ on 11 μm) caused difference in the interaction mechanisms. More in detail, at high Le values (0.6 J/mm), the depth rapidly drops for increasing pulse energy after a Pe > 0.28 mJ (or equivalently a pulse power > 8 kW), in agreement to what observed by Wlodarczyk et al.…”
Section: Groove Profile Geometrysupporting
confidence: 54%
“…It can be concluded that the mechanisms involved in the mark formation, as well as the contrast, are more complex than those suggested in [35][36] and a higher number of parameters must be taken into account, as also suggested by several authors [19][20][21] . So, in order to analyse the effect of the process parameters on the mark geometrical characteristics, statistical analysis (ANoVA and RSM) was performed.…”
Section: Groove Profile Geometrymentioning
confidence: 66%
See 1 more Smart Citation
“…Интересным решением, нашедшим применение в лазерной маркировке металлов, является воздействие на поверхность металла сфокусированным наносекундным излучением [13]. В этой работе маркировка осуществлялась лазерными пятнами с выраженным кратерообразованием.…”
Section: обсуждение результатовunclassified
“…Therefore, those materials can be divided in two classes regarding its linear absorption with respect to the pump excitation wavelength. Within the class of opaque materials, specifically for metals, the high spatially selective ablation obtained with fslaser microstructuring have been used, for example, for repairing photolithography masks 6 , hole drilling 7 , production of reflecting computer generated holographic for security [8][9] or beam control [10][11] , maskless alternative fabrication of interdigitated electrodes for faster prototyping 12 , nanoparticles generation 13 and producing superhydrphobic surfaces. 14 Still on non-transparent materials, such as linearly absorbing semiconductors, their surface topography and properties have also been modified by ultrashort pulses.…”
Section: Introductionmentioning
confidence: 99%